Perilaku petani dalam penggunaan pestisida dan alat pelindung diri (APD) serta keluhan kesehatan petani di desa suka julu kecamatan barus jahe kabupaten karo tahun 2014 - Roy maranata; indra chahaya; devi nuraini santi (Lingkungan dan Kesehatan Kerja, 2014)
Most of people who live in Karo are farmer. They are using pesticide to maintain their farm. They using of pesticide which does not meet the procedures causes many impact. Such as poisoning for farmers. The purpose of this research is describe the behavior of farmer using pesticides having personal protective equipment (PPE) and health complaints of farmer in Suka Julu Kecamatan Barus Jahe Kabupaten Karo. The type this research was descriptive with 95 person as samples. The sampling technique was purposive sampling. The result of this research about the characteristic of farmers, were over 30 years old farmers were 78 person (82,1%), male farmers were 62 person (65,3%), Senior high school farmers were 82 person (86,3%) frequency in using pesticide more than 3 times a week 58 person (61,1%), application pesticide in the morning was 77 person (81,1%). Farmer whose good knowledge were 22 person (23,2%), farmers whose good manner were 83 person (87,4%), farmers whose good practice were 87 person (91,6%). The characteristic of pesticide based on liquid formula was 62 person (65,3%). The type of pesticide was insecticide is 52 person (54,7%). The farmer whose application carbamate pesticide were 44 person (46,3%), The dossage which not suggested is 63 person (66,3%). Respondents whose health complaints caused by pesticide in the last one week are 77 person (81,1%). The symptoms caused by using pesticide was headache which were 56 person (58,9%), dizziness which is 64 person (67,4%), nausea which were 66 person (69,5%), watery eyes which were 75 person (78,9%). The suggested to farmers to use pesticide and having personal protective equipment (PPE) properly as already set in the procedure and the recommendation. Keywords :Behavior, Pesticides, Personal Protective Equipment, Health Complaints